Industrial Internet Federated Learning Driven by IoT Equipment ID and Blockchain - Zhang, Xu; Hou, Haibo; Fang, Zhao; Wang, Zhiqian (Wireless communications and mobile computing, 2021)
With the development of Internet of Things (IoT), 5G, and industrial technology, Industrial Internet has become an emerging research field. Due to the industrial specialty, higher requirements are put forward for time delay, safety, and stability of the identification analysis service. The traditional domain name system (DNS) cannot meet the requirements of industrial Internet because of the single form of identification subject and weak awareness of security protection. As a solution, this work applies blockchain and federated learning (FL) to the industrial Internet identification. Blockchain is a decentralized infrastructure widely used in digital encrypted currencies such as Bitcoin, which can make secure data storage and access possible. Federated learning protects terminal personal data privacy and can carry out efficient machine learning among multiple participants. The numerical results justify that our proposed federated learning and blockchain combination lays a strong foundation for the development of future industrial Internet.